Age specific evaluation of sexual behavior, STI knowledge and infection among asymptomatic adolescents and young adults. Issue 8 (August 2020) - Skaletz-Rorowski, A.; Potthoff, A.; Nambiar, S.; Wach, J.; Kayser, A.; Kasper, A.; Brockmeyer, N.H.
Abstract: Objectives: Adolescents and young adults account for 50% of new infections with sexually transmitted infection (STI), while representing only 25% of the sexually active population. An evaluation of sexual behavior, STI knowledge and infection among youth of different age groups is relevant to formulate effective sexual health strategies. Methods: In this monocentric, open, prospective cross-sectional study, 268 asymptomatic subjects (14–30 years) were partitioned into three cohorts I: 14–19 ( n  = 42), II: 20–25 ( n  = 147) and III: 25-30 ( n  = 79) years. A comparative analysis of their sexual behavior and STI knowledge was performed using a 21-item questionnaire at the WIR-Center for Sexual Health and Medicine. Prevalence of chlamydia and gonococcal infections were tested, using the Cepheid Xpert® CT/NG assay. Results: The three age-specific cohorts showed statistically significant differences in their relationship status, their sexual contacts and the number of life-time sexual partners. Independent of age, men who have sex with men had greater number of sexual partners across all age groups. Although >95% of participants were aware of HIV in all age groups, the corresponding awareness of non-HIV STI was consistently lower in cohort I. The awareness of trichomonas, mycoplasma and candida in particular was <50% across all agedemographies. Chlamydia screening remains poor despite current chlamydia infection among cohort I, II & III being 7.1%, 5.4%, & 11.4% respectively. Conclusion: Our study demonstrates a demographic divide in the knowledge on most frequent STI apart from HIV. Current education, screening and vaccination programs for STI among the younger demographic should be improved.